Influence of seed size and aging on seedling growth and field establishment of lentil (Lens culinaris Medik) - Ghassemi-Golezani, Kazem; Chadordooz-Jeddi, Afsaneh; Zehtab-Salmasi, Saeid; Oustan, Shahin (Plant Breeding and Seed Science, 2012)
A sub-sample of lentil (Lens culinaris Medik. cv. Kimia) seeds was kept as bulk (S1) and the other seeds were separated by a sieve with four millimeters diameter. Consequently, three seed lots including bulk (S1), large (S2) and small (S3) seeds were obtained. Seeds of each size were divided into three sub-samples. A sub-sample was kept as control or high vigor seed lot (A1). The other two sub-samples with about 20% moisture content were artificially aged at 40°C for 2 and 4 days (A2 and A3, respectively). These seeds were evaluated in laboratory and field during 2011 and 2012 as factorial experiments on the bases of RCB design. The lowest mean germination and emergence times and the highest germination percentage, seedling dry weight and emergence percentage were recorded for high vigor seed lot. Large seeds produced the largest seedlings in comparison with bulk and small seeds. Although, seedling dry weight was reduced with increas- ing seed aging, the lowest reduction was recorded for seedlings from large seeds. The most deteriorated large seeds germinated earlier than those of bulk and small seeds. Early germination of the most deteriorated large seeds resulted in rapid emergence of seedlings in the field. This is also reflected in the highest positive correlation of mean germination time with mean emergence time. It was concluded that some deleterious effects of seed aging can be reduced by increasing seed size.